Working With PhD Students to Build Their Transferability and Researcher Skills in the FEASST@8 and SuCCEED@8 Projects. Issue 163 (3rd September 2019) - Devecchi, Cristina
Abstract: Providing doctoral students with the employability skills they needs is a developing area rich with a variety of training opportunities. This contribution argues that including students as co‐researchers through a process of "learning by doing" enables them to learn and implement new skills in a safe but risk‐taking environment.